The emotional involvement of physicians in the Oncology Intensive Care Unit: a phenomenological-hermeneutic study - Tringali, Debora; Carli, Bernardo; Chelazzi, Cosimo; Villa, Gianluca; Lanini, Iacopo; Bianchi, Antonio; Amato, Alessandra; Romagnoli, Stefano; Lauro Grotto, Rosapia (Frontiers in Psychology, 2024)
Background This phenomenological-hermeneutic study is about the experiences of physicians in the Oncology Intensive Care Unit of the Careggi University Hospital, in Florence. The Oncology Intensive Care Unit is a place of great emotional impact and can be create stressful situations. The emotional labor can lead to the development of cynicism, depersonalization and emotional exhaustion. The objective of the study was to learn about and come into contact with the experiences of operators who operate in a highly specialized and critical context. Method A semi-structured interview was conducted on 11 physicians in the Oncology Intensive Care Unit of careggi hospital. The interviews were transcribed and subjected to content analysis using the phenomenological-hermeneutic method. The results concerning the emotional involvement of doctors were placed in three macro categories: difficulties, what helps and needs. Results The interviews highlight the difficulty doctors have in coming into contact with the potentially deadly disease and a further aggravating element appears to be the identification with the patient himself. This condition of difficulty can lead doctors to commit medical errors or to reduce the quality of care. Conclusion The results that emerged provide a more detailed understanding of the landscape of emotional reactions of working with the cancer patient in the intensive care unit. In light of the high emotional burden and the inherent possibility of developing burnout in this target population of health care workers, knowing the main critical issues and needs reported may facilitate a more effective tailored intervention.